2019
DOI: 10.1002/eat.23074
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and bulimia nervosa in the United States

Abstract: Background: Food insecurity occurs when access to food is limited by financial hardship.Yet, paradoxically, food insecurity is associated with overeating, with emerging evidence that it may be related to disordered eating. A recent report found that food insecurity was associated with binge-eating disorder (BED), but it is not yet known whether food insecurity is also associated with bulimia nervosa (BN).Methods: Participants were 873 respondents recruited online who completed a battery of established measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 22 publications
1
56
1
1
Order By: Relevance
“…Food insecurity has also been found to be cross-sectionally associated with specific ED diagnoses (as assessed via self-report questionnaire) in an adult sample recruited online [ 55 ••, 56 ••]. Using participants with body mass indexes less than 25 kg/m 2 as the referent group, Rasmusson and colleagues found food insecurity to be associated with binge-eating disorder [ 55 ••], and Lydecker and colleagues found food insecurity to be associated with bulimia nervosa [ 56 ••].…”
Section: Emerging Evidence For a Link Between Food Insecurity And Eatmentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity has also been found to be cross-sectionally associated with specific ED diagnoses (as assessed via self-report questionnaire) in an adult sample recruited online [ 55 ••, 56 ••]. Using participants with body mass indexes less than 25 kg/m 2 as the referent group, Rasmusson and colleagues found food insecurity to be associated with binge-eating disorder [ 55 ••], and Lydecker and colleagues found food insecurity to be associated with bulimia nervosa [ 56 ••].…”
Section: Emerging Evidence For a Link Between Food Insecurity And Eatmentioning
confidence: 99%
“…Food insecurity has also been found to be cross-sectionally associated with specific ED diagnoses (as assessed via self-report questionnaire) in an adult sample recruited online [ 55 ••, 56 ••]. Using participants with body mass indexes less than 25 kg/m 2 as the referent group, Rasmusson and colleagues found food insecurity to be associated with binge-eating disorder [ 55 ••], and Lydecker and colleagues found food insecurity to be associated with bulimia nervosa [ 56 ••]. For simplicity and ease of interpretability in this review, we have used the raw numbers reported in these studies [ 55 ••, 56 ••] to calculate prevalence estimates in the full sample of 1329 participants, irrespective of weight status.…”
Section: Emerging Evidence For a Link Between Food Insecurity And Eatmentioning
confidence: 99%
“…Alternately, many researchers and clinicians who treat eating disorders emphasize the central role of rigid and rule-bound eating habits (e.g., "food rules") in maintaining eating disorder symptoms and that any attempt to restrict dietary intake can set the stage for the onset of an eating disorder, even if the initial restriction is not motivated by weight and shape concerns (e.g., Gilbody et al, 1999;Polivy, Herman, Younger, & Erskine, 1979). A similar argument has been made about the etiological role of non-weight-related restrictive eating due to food insecurity, in light of recent findings showing that people who are food insecure report elevated disordered eating symptoms and behaviors that increase with increasing levels of food insecurity (Becker, Middlemass, Taylor, Johnson, & Gomez, 2017;Lydecker & Grilo, 2019).…”
mentioning
confidence: 92%
“…The occasion of the COVID-19 global pandemic has driven a sudden shift to online healthcare delivery [38], alongside increased rates of mental health complaints and worsening anxiety and depression [39,40]. Those suffering from eating disorders are particularly vulnerable during times of food insecurity, with lack of access to "safe" foods combined with erratic food distribution causing a 'feast or famine' pattern de ned by hoarding, restriction, bingeing and compensation [41,42]. There is evident emergent need, then, for novel online risk-assessments and screening options suitable for self-referral, where the burden of mental health is increasing while face-toface access to physicians is curtailed by social distancing measures [43,44].…”
Section: Introductionmentioning
confidence: 99%